Thermal ablation of mucosal defect margins to prevent local recurrence of large colorectal polyps: a systematic review and meta-analysis - Meulen, Lonne W.T.; Bogie, Roel M.M.; Winkens, Bjorn; Masclee, Ad A.M.; Moons, Leon M.G. (Endoscopy International Open, 2022)
Background and study aims Endoscopic mucosal resection of large non-pedunculated colorectal polyps is characterized by a high risk of recurrence. Thermal ablation of the mucosal defect margins may reduce recurrence in these lesions, but a systematic overview of the current evidence is lacking.Methods We searched PubMed, Embase and Cochrane until July 2021, for studies on thermal ablation of mucosal defect margins of large non-pedunculated colorectal polyps. Main goal of this meta-analysis was to identify pooled risk difference of recurrence between thermal ablation vs. no adjuvant treatment. Secondary goal was to identify pooled recurrence rate after snare tip soft coagulation (STSC) and argon plasma coagulation (APC).Results Ten studies on thermal ablation of mucosal defect margins were included, with three studies on argon plasma coagulation, six studies on snare tip soft coagulation and one study comparing both treatment modalities, representing a total of 316 APC cases and 1598 STSC cases. Overall pooled risk difference of recurrence was –0.17 (95 % confidence interval [CI] –0.22 to –0.12) as compared to no adjuvant treatment. Pooled risk difference was –0.16 (95 % CI –0.19 to –0.14) for STSC and –0.26 (95 % CI –0.80 to 0.28) for APC. Pooled recurrence rate was 4 % (95 % CI 2 % to 8 %) for STSC and 9 % (95 % CI 4 % to 19 %) for APC.Conclusions Thermal ablation of mucosal defect margins significantly reduces recurrence rate in large non-pedunculated colorectal lesions compared to no adjuvant treatment. While no evidence for superiority exists, STSC may be preferred over APC, because this method is the most evidence-based, and cost-effective modality.